Fulfillment of Special Needs of Women Prisoners and Detainees: A Study in 12 Women Penitentiaries - Lilis Lisnawati; Nadia Utami L; Gatot Goei (Yayasan Jurnal Perempuan, 2017)
Just like others, women undergone an imprisonment sentence also have specific women needs relating to biological, psychological condition, and the vulnerability as a woman. In Indonesia, the government commitment in fulfilling the special needs has started with the signing of a number of national and international regulations. The materialization of the commitment ismandated to the Ministry of Law and Human Rights, in this case is the Directorate General of Corrections that has a job and function relating to criminal execution. To see the seriousness of the government in executing the commitment, the Center for Detention Studies did a surveyon the quality of correctional service in 12 women penitentiaries involving 385 women inmates and 35 women detainees in 4 (four) different periods in between 2013-2015. The result shows that the commitment to provide the women special needs has not yet been done well. The strong patriarchal paradigm considering that women are not supposed to commit any crime causes some components in women detention to be not gender-sensitive yet. The shape of the building and the facilitation pattern shows that women are not expected to become an occupant of detention facility. As the consequence, the specific needs of women spending their time in detention facility are neglected.